2010
DOI: 10.1111/j.1757-7861.2009.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of brachial plexus injury with modified contralateral C7transfer

Abstract: The method of partial C(7) root transfer results in equally good motor function as does transfer of the whole root, while occurrence of motor and sensory damage is less than that which occurs with transfer of the whole root.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…7, 1034 The studies were divided into whole CC7 (n=16) and partial CC7 (n=11). Three studies reported two CC7 types, 9, 12, 25 and the CC7 type was not available in 3 studies 10, 13, 33 that were only included in overall study (Table 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7, 1034 The studies were divided into whole CC7 (n=16) and partial CC7 (n=11). Three studies reported two CC7 types, 9, 12, 25 and the CC7 type was not available in 3 studies 10, 13, 33 that were only included in overall study (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“… § N, number; y, year; mo, month; † Three studies 9, 12, 25 reported two CC7 types, and the CC7 types were not available in 3 studies 10, 13, 33 , so there were 27 studies. …”
Section: Figurementioning
confidence: 99%
“…It's effective in restoring partial sensation of hand,wrist and finger flexion without permanent sensory and motor damages to the healthy side [3,9]. Because the number of myelinated nerve fibers of cC7 root is much more than that of any recipient nerve including radial nerve, median nerve or musculocutaneous nerve, some scholars have tried to repair two recipient nerves simultaneously by cC7 transfer [7,24,25,27]. They have found that both of the two recipient nerves have achieved recoveries.…”
Section: Introductionmentioning
confidence: 99%
“…It's effective in restoring partial sensation of hand ,wrist and finger flexion without permanent sensory and motor damages to the healthy side. 3,9 Because the number of myelinated nerve fibers of cC7 root is much more than that of any recipient nerve including radial nerve, median nerve or musculocutaneous nerve, some scholars have tried to repair two recipient nerves simultaneously by cC7 transfer 7,24,25,27 . They have found that both of the two recipient nerves have achieved recoveries.…”
Section: Introductionmentioning
confidence: 99%